Pengaruh E-Service Quality dan E-Trust terhadap Continuance Intention melalui E-Satisfaction sebagai Variabel Mediasi (Studi pada Aplikasi Access By KAI) - Arfiansyah, Valdi; Widyastuti (Jurnal Ilmu Manajemen, 2024)
PT Kereta Api Indonesia (Persero) has developed the latest application change for ordering and booking train tickets from KAI Access to Access by KAI on August 10 2023. It can be seen that the KAI application's Customer Satisfaction Index (CSI) in 2023 will reach 4, 14 (very good). However, according to the Google Play Store and App Store review ratings in 2023, user satisfaction with the Access by KAI application is very low, with an average score of 2.1 (Google Play Store) and 1.5 (App Store). This research aims to discuss and analyse the influence of e-service quality and e-trust on continuance intention through e-satisfaction as a mediating variable in the Access by KAI application. This quantitative research uses path analysis statistics by taking a sample of 200 respondents using a non-probability sampling approach with purposive sampling. The findings of this research indicate that e-satisfaction is significantly influenced by e-service quality and e-trust. In addition, continuance intention is significantly influenced by e-service quality and e-satisfaction but not by e-trust. In addition, e-satisfaction mediates the relationship between e-service quality and e-trust on continuance intention. The implications of this research provide valuable insight for PT KAI to understand how improving e-service quality and e-trust can contribute to the continuance intention of application users. PT KAI can also design a marketing strategy that focuses on increasing e-satisfaction to ensure that increasing e-service quality and e-trust can influence the continuance intention of application users.